Kualitas Hidup Sibling Anak dengan Autis - Ikeu Nurhidayah; Sri Hendrawati; Yuli Anggia (Jurnal Keperawatan Silampari, 2020)
This study aims to identify the quality of life picture of sibling children with autism. The research design uses quantitative descriptive methods. The results showed as many as 17 people (51.51%) included in the first category, while as many as 16 people (48.48%) were included in the wrong category. There are two dimensions of quality of life that are still involved in the wrong group, namely the emotional aspect and the school dimension. Conclusion, quality of life will affect sibling growth and development so that efforts can be made to maintain and improve the quality of life of sibling children with autism through health education to sibling related to how to deal with the condition of children with autism and to families regarding the importance of social support for sibling children with autistic. Keywords: Autism, Quality of life, Sibling